Petrological and Geochemical Characteristics of Pyroclastics Outcropping in Abakaliki Area Lower Benue Trough, Nigeria (Global Journal of Science Frontier Research, 2013)
Bakaliki pyroclastics are part of the volcanoclastics of the Lower Benue Trough Nigeria. The petrological and geochemical study of the pyroclastics was carried out; to evaluate and re-appraise their petrology, stratigraphic position and origin which have remained subjects of controversy in the Benue Trough Geology. The pyroclastics outcrop as enlongate and domical bodies that are large and massive. Field relationships indicate that the volcanoclastics occur within the Abakaliki Shale of the Asu River Group and in some places they interbed with the shales. They occur mostly as agglomerates and welded tuffs cut by several quartz filled veins and segregations. The agglomerates are porphyritic with angular fragments of shales embedded in them. The tuffs are very fine grained and aphanitic in texture. Petrographic data obtained from this study show plagioclase and augite as the major mineral constituents with quartz, olivine, calcite and iron oxide as the accessories. Devitrified glass shards are common in the rocks. They are of basaltic composition. Geochemical analysis shows that the pyroclastics are subakaline, tholeiitic rocks of thin continental crust origin. They are classified as basalts, basaltic andesites, dacites and rhyolites.
Keywords: abakaliki pyroclastics; benue trough; petrography; geochemistry